PERAN PENYULUH PERTANIAN DALAM PENGENDALIAN ORGANISME PENGGANGU TANAMAN KENTANG (Solanum tuberosum L.) DI KECAMATAN SIRAMPOG KABUPATEN BREBES - Mudmainah, Siti (JURNAL AGRIMANSION, 2025)
The research locatian was chosen purposively. This research was conducted in potato croos in Sirampog district, Brebes Regency. The research method used was a combination of qualitative and quantitative descriptive methods. Respondent samples taken in this research were 5 agricultural extension workers and 97 respondents from 1.744 farmers. This research was conducted from November 2022 to August 2023. The results of this study note that there were seven roles in agricultural extension activities in Sirampog District, namely the role of education dissemination of innovation, facilitation, consultation, supervision, monitoring and evaluation. Agricultural extension workers in Sirampog District received a good response from farmers because farmers felt they were assisted in increasing the agricultural potential of the region and increasing their human resources. Based on the research results, the role of education obtained the highest percentage score, namely 14.70%, was period, because agricultural extension workers directly educate farmers about good farming systems, dosage of fertilizer use, use of agricultural technology, and disease control. The evaluation role obtained the lowest score, which was 14.04%, period capital because it was suspected that farmers rarely met with agricultural extension officers evaluation activities rarely occurred for some farmers who did farming. The results showed that the role of agricultural extension agents in controlling plant pest organist in potato plants had a good role as seen from the role of extension agents as educators, disseminators of inovators , facilitators, colsultation, supervisors, monitorors and evaluators which had an impact on reducing yield losses caused plant pest organist so as in helping to increase potato production.